2013
DOI: 10.1002/2013jg002320
|View full text |Cite
|
Sign up to set email alerts
|

Variations in high‐latitude riverine fluorescent dissolved organic matter: A comparison of large Arctic rivers

Abstract: [1] Given the pace of climate change, it is important to better understand dissolved organic matter (DOM) storage and cycling in high-latitude rivers and its subsequent export to the Arctic Ocean. To address this concern, excitation/emission matrix spectroscopy and parallel factor analysis (PARAFAC) coupled with optical indices were used to characterize the optical properties of fluorescent DOM (FDOM) and colored DOM (CDOM) in five large Arctic rivers over two seasonal cycles. Five PARAFAC components were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
125
7
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(168 citation statements)
references
References 61 publications
23
125
7
1
Order By: Relevance
“…with earlier results (Spencer et al, 2009;Stedmon et al, 2011;Walker et al, 2013). The raw EEMs acquired with Aqualog R were corrected for inner-filter effects and for the Raman and Rayleigh scattering (Murphy et al, 2013).…”
Section: Doc and Dom Sample Processing And Data Analysismentioning
confidence: 83%
See 1 more Smart Citation
“…with earlier results (Spencer et al, 2009;Stedmon et al, 2011;Walker et al, 2013). The raw EEMs acquired with Aqualog R were corrected for inner-filter effects and for the Raman and Rayleigh scattering (Murphy et al, 2013).…”
Section: Doc and Dom Sample Processing And Data Analysismentioning
confidence: 83%
“…The Lena Delta region and Laptev Sea have high DOC concentrations (>500 µM) and high CDOM associated with low salinity waters (Alling et al, 2010;Stedmon et al, 2011;Semiletov et al, 2013;Walker et al, 2013;Heim et al, 2014;Dubinenkov et al, 2015a), decreasing toward higher salinities through conservative mixing (Cauwet and Sidorov, 1996;Kattner et al, 1999). This is a characteristic also thought to be shared by other Arctic rivers (Dittmar and Kattner, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…The riverine input can be monitored by optical methods with absorption, fluorescence, or remote-sensing measurements (Spencer et al, 2012;Walker et al, 2013;Fichot et al, 2013;Mann et al, 2016). The largest DOC concentrations were found in the Siberian rivers Lena -1300 µmol L −1 , Yenisey -842 µmol L −1 , and Ob -950 µmol L −1 , and the concentrations were lower in the North American Yukon -816 µmol L −1 and McKenzie -648 µmol L −1 rivers Mann et al, 2016).…”
Section: Relationship Between Cdom Absorption and Docmentioning
confidence: 99%
“…In the spring and summer seasons, DOC found in rivers shows signs of more terrestrial inputs (i.e., increased lignin phenols) [159], suggesting a more connected landscape where water carries solutes from all regions of a watershed. Further, the IPCC has predicted that runoff resulting from the thawing of permafrost in the arctic and subarctic areas and subsequent formation of new ponds and lakes will increase the availability of stored carbon stocks [121] through increased hydrologic connectivity [160]. As permafrost thaws, the hydrologic connectivity of arctic and subarctic regions will increase, resulting in greater export of allochthonous DOC to fluvial networks, and ultimately, to the ocean.…”
Section: Changing Hydrology and Its Effect On Doc Concentrationsmentioning
confidence: 99%
“…Likewise, phenolic portions of humic acids from the International Humic Substance Society (IHSS) were identified with fluorescence/PARAFAC and reagent-based phenol assays [53] and lignin phenols found in several large artic rivers have been attributed to a PARAFAC-derived component [160]. In kinetic studies of THM formation upon chlorination of natural waters, it was shown that resorcinol components make up 15%-30% of THM precursors in natural water and are likely fast reacting (formed within first hours) THM precursors [4], while other phenolic compounds are likely slow reacting (from hours to weeks) THM precursors [4].…”
Section: The Impact Of Increased Doc On Drinking Water Supply and Trementioning
confidence: 99%